MULTIOMICS INTEGRATION IN ANTI-TUBERCULOSIS DRUG DISCOVERY - Yaro, Abubakar (Sanamed, 2025)
Despite intensive global efforts, tuberculosis remains one of the leading global health burdens, with antimicrobial resistance being a significant challenge to managing the disease. In addition, the current drugs used to treat tuberculosis suffer from limitations, such as prolonged therapeutic duration and toxicity. Therefore, the development of new anti-tuberculosis drugs is a priority. However, this process faces several challenges. The introduction of a multiomics approach could serve as an ideal platform to accelerate drug development by addressing these challenges. This article reviews the potential role of multiomics in anti-tuberculosis drug development and briefly discusses the associated challenges in utilizing multiomics for drug discovery.